Cohousing For Whom? Survey Evidence to Support the Diffusion of Socially and Spatially Integrated Housing in the United States. Issue 5 (3rd September 2018) - Boyer, Robert H. W.; Leland, Suzanne
Abstract: Cohousing is a resident-led neighborhood development model that clusters private dwelling units around collectively owned and managed spaces, with potential to address long-term social and environmental challenges in American metropolitan regions. To date, however, the cohousing model has been slow to diffuse beyond a demographically narrow following. This limited following may signal to policymakers that cohousing is an unappealing housing model, and therefore an impractical policy objective. Drawing from a survey of 1, 000 American residents, the results of a multivariate regression model suggest that (a) many of the characteristics of the current resident population of cohousing in the United States have no statistical association with the individuals who indicate interest in cohousing nationwide; (b) other characteristics serve as better predictors of interest in cohousing; and therefore (c) the slow diffusion of cohousing is likely the consequence of inaccessibility rather than low appeal. Overcoming these challenges demands shifts in policy.